Relationship Between Loneliness and Grade Point Average (GPA) During Online Learning Among Medical Students at Universitas Islam Negeri (UIN) Jakarta - Fikrifar Rizki Faridho; Ahmad Yurdiansyah (Universitas Ibn Khaldun Bogor, 2026)
The Coronavirus Disease 2019 (COVID-19) pandemic has led the world to change its daily activities by prioritizing safety, one of which is by implementing health protocols. Most higher educational institutions were required to carry out the learning process using an online system, commonly referred to as the Remote Learning System, which was implemented without face-to-face meetings to prevent crowds in one room (class). This policy is stated in Circular Letter Number 4 of 2020 concerning the Implementation of Education in COVID-19. Loneliness is one of the emerging issues during the COVID-19 pandemic. We found adolescents and young adults have a higher risk of loneliness (27%) during the COVID-19 pandemic. This study is an analytical study with a cross-sectional method, which aims to find out the relationship between loneliness and Grade Point Average (GPA) among medical students at Universitas Islam Negeri (UIN) Jakarta enrolled in 2019 during the online learning period. The results of the study in 82 respondents showed that 17.1% of students were not lonely, 58.5% experienced mild loneliness, 22.0% experienced moderate loneliness, and 2.4% experienced severe loneliness. The hypothesis test using Kruskal-Wallis obtained a p-value of 0.707 (>0.05), indicating no significant relationship between the level of loneliness and GPA during online learning among medical students at UIN Jakarta, enrolled in 2019. Further study is suggested to use larger samples and apply other variables, other than the level of loneliness, that may influence the GPA among medical students during online learning.